Home on huckleberry hill eaudiobook - Beckstrand, Jennifer (Matchmakers of Huckleberry Hill, 2019)
Huckleberry Hill, Wisconsin's irrepressible eighty-something matchmakers Anna and Felty Helmuth are at it again. And this time they're willing to rough it to get the job done . . . Mary Anne Neuenschwander knows she should be content with what Gotte has given her. She has a comfortable house, a fruitful farm, and a good, steady husband. But after nearly six years of marriage, she still longs for a baby. Yet her husband, Jethro, seems to care more about fishing than about his wife. Unable to bear Jethro's indifference, Mary Anne moves into a tent in the woods where he won't have to be bothered. But when her mammi and dawdi find out what she's done, they'll stop at nothing—including a little camping trip of their own—to help save their granddaughter's marriage . . . Jethro's greatest blessing is his beloved wife, Mary Anne. Nothing else in his life has turned out anywhere near the way he expected. Rather than burden Mary Anne with his disappointment, he shields her by spending less and less time at home and more time on the river. But when he finds that she's moved out, he's shocked. What will people think? What is Mary Anne thinking? And what clever plans are her grandparents hatching? . . .